Development of Science Teaching Materials Based on Augmented Reality on Energy Material in Living Systems - Muh Syarif S Abd Syukur; Nur Rahmah; Pahriadi Pahriadi (CV. Dharma Samakta Edukhatulistiwa, 2025)
The nature of Natural Science as a science that originates from nature and has several abstract concepts that cannot be presented directly into the classroom is a challenge for teachers to convey these concepts. The rapid development of technology allows humans to interact directly without being limited by space and time. One technology that can be used to visualize several abstract concepts in science lessons is augmented reality. This study aims to develop science teaching materials based on Augmented Reality (AR) on the material of energy in life systems. This type of research is development research referring to the development of Borg & Gall which was modified from (Sugiyono, 2014). This study consists of 10 stages, namely (1) Potential and Problems; (2) Data Collection; (3) Product Design; (4) Product Design Validation; (5) Product Design Revision; (6) Product Trial; (7) Product Revision; (8) Usage Trial; (9) Product Revision; and (10) Mass Production. By implementing all these stages, it is expected to produce science teaching materials based on Augmented Reality that are valid and reliable based on expert responses and trial results. The output of this study is a research article published in an accredited national journal and HAKI science teaching materials based on Augmented Reality.